Jane Austen's literary manuscripts : a study of the novelist's development through the surviving papers - Southam, B. C. (Continuum studies in Jane Austen., 2001)
Jane Austen''s Literary Manuscripts remains the definitive account of the novelist''s surviving papers. These date from 1787 to 1817, from the first beginning to the veyr end of her writing career. Their evidence considerably deepens our understanding of the imaginative process that stands behind the composition of the great novels. In Sanditon, the last work, we see the promise of a further and startling development in her art. The influence of her childhood reading and home life is considered in the first chapter, and a further new chapter examines Sir Charles Grandison, a work newly attribu.